Interference Between Family Caregivers' Mental Disorders and Their Estimates of Quality of Dying and Death (QODD) of Their Loved Ones. Issue 1 (January 2017) - Heckel, Maria; Bussmann, Sonja; Weber, Martin; Ostgathe, Christoph; Stiel, Stephanie
Background: In studies enrolling informal caregivers of patients in palliative care, it is necessary to ensure that findings are not influenced by factors such as mental disorders. Aim: This study aims to describe the influence of anxiety and depression on bereaved informal caregivers' retrospective ratings of the quality of dying and death (QoDD) of their loved ones. Design: Informal caregivers of deceased patients from 2 German palliative care (PC) units took part in a validation study of the German version of the original QoDD-Deutsch-Angehörige (QoDD-D-Ang) during the fourth week following the patient's death at the earliest. Depressive and panic disorders were assessed via the Patient Health Questionnaire (PHQ). Group comparisons (χ 2, t test; significance level P < .05) analyzed whether informal caregivers with depression or panic disorders and those without such disorders differ in their estimates. Results: A total of 226 informal caregivers participated between August 2012 and December 2013. The mean age of participants was 55.5 years; 61.1% were female. The PHQ of 221 participants resulted in 8.6% with major disorders, 13.6% with other depressive syndromes, and 77.8% without depressive disorders. In this secondary data analysis here, there was no difference between female and male participants concerning the incidence of depression ( P = .519, χ 2 ). Two participants screened positive for both panic and major depressive disorders. Both groups presented no significant differences in the mean total QoDD-D-Ang scores ( P = .343). Conclusion: Informal caregivers' estimates on the QoDD-D-Ang of their significant others do not interfere with mental disorders. Therefore, bereaved informal caregivers are able to participate in the PC research after a few weeks following the loss of a loved one.